Sclerochronological Study of a Glycymeris vangentsumi Population From the Madeira Islands - Németh, Alexandra; Kern, Zoltán (Frontiers in Earth Science, 2018)
Despite the positive results obtained using saltwater clam Glycymeris spp. for palaeoenvironmental reconstructions in the extratropical North Atlantic domain, this potential of the species has not been investigated in the subtropical North Atlantic region. The aim of this study was to investigate the driving factors for shell growth in Glycymeris bivalves by analysing growth patterns of G. vangentsumi specimens from an environment that is exposed to relatively minor seasonal contrast in terms of temperature compared to mid/high latitudes around the Madeira Islands. The populations studied comprised a group of sub-fossil shells (n=58) collected near the Desertas Islands, Madeira, in 2014, in a depth range of 80-160 m, together with two live-caught specimens. The shells collected alive were relatively young (<37 years), while the ontogenetic ages of the sub-fossil shells proved to be high (up to 154 years). Compared to those collected at greater depths, the average growth rate of the shells in the shallower environment was higher in the first four years. Subsets of the Madeira (n=16) samples could be arranged into a robust site chronology covering the 1950-2012 period, and these were used to explore shell growth responses to environmental parameters. The composite chronology displayed a negative correlation (r<-0.58, p < 0.01) with the January-April sea surface temperature (SST) around Madeira and a positive correlation (r=0.52, p<0.05) with the March sea surface chlorophyll concentration data of the region, from 1998 to 2012. The results presented here suggest that at this southern collection site, lower water temperature was not a directly limiting environmental variable, and other external environmental effects may exert stronger control on shell growth. These include the effect of late winter ocean mixing on the formation of the deep chlorophyll maximum.